2019
DOI: 10.1590/1678-4324-2019170813
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production Of Streptokinase By Chemical Mutagenesis Of Streptococcus agalactiae EBL-20

Abstract: Streptokinase (SK) is an enzyme that is used for the treatment of cardiovascular diseases. The current study focused on the enhanced production of SK by inducing mutation in Streptococcus agalactiae EBL-20 and optimization of medium components and culture conditions for the maximum growth of mutant derived strain. S. agalactiae EBL-32 was selected as a potent mutant after exposure of S. agalactiae EBL-20 to EMS for 180 minutes. SK activity obtained from mutant derived strain was found to be 1.6 fold higher as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some have used Streptococcus agalactiae with nonspecific ethyl methanesulfonate (EMS) based chemical mutagenesis [44], Streptococcus sanguis produced lowered molecular mass containing streptokinase [45], B. sublitis with C-terminally processed streptokinase [46]. Relative comparison of streptokinase activity in different hosts was as follows, Saccharomyces pombe (2450 IU), Streptococcus equisimilis (100-150 IU), Pichia pastoris (3200 IU) and E. coli (1000-1500 IU) [44,[47][48][49]. All these studies observed that streptokinase degradation of matured streptokinase 47kDa to inactivated 44kDa [45,46,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have used Streptococcus agalactiae with nonspecific ethyl methanesulfonate (EMS) based chemical mutagenesis [44], Streptococcus sanguis produced lowered molecular mass containing streptokinase [45], B. sublitis with C-terminally processed streptokinase [46]. Relative comparison of streptokinase activity in different hosts was as follows, Saccharomyces pombe (2450 IU), Streptococcus equisimilis (100-150 IU), Pichia pastoris (3200 IU) and E. coli (1000-1500 IU) [44,[47][48][49]. All these studies observed that streptokinase degradation of matured streptokinase 47kDa to inactivated 44kDa [45,46,50].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the expression of streptokinase with different expression vectors/strategies and the host are available. Some have used Streptococcus agalactiae with nonspecific ethyl methanesulfonate (EMS) based chemical mutagenesis [44], Streptococcus sanguis produced lowered molecular mass containing streptokinase [45], B. sublitis with C-terminally processed streptokinase [46]. Relative comparison of streptokinase activity in different hosts was as follows, Saccharomyces pombe (2450 IU), Streptococcus equisimilis (100-150 IU), Pichia pastoris (3200 IU) and E. coli (1000-1500 IU) [44,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Next, by inducing the expression vector, high expression of the recombinant protein recSK was produced which held little or no capacity to react as an immunogen (Deepak & Geetha, 2019). Another study carried out by (Arshad, Zia, Asghar, & Joyia, 2019) in an attempt to achieve the said objective, enhanced production of streptokinase was obtained with little immunogenicity by chemical mutagenesis of S. agalactiae.…”
Section: Streptokinasementioning
confidence: 99%
“…The microbial synthesis of streptokinase has been further reported to increase using mutant microbial species and optimization of fermentation medium. Arshad et al, (2019) reported a 4.14-fold increase in streptokinase production by optimization of fermentation media. Similarly, Wu et al, (2019) developed a cheap fermentation media for the cost-effective synthesis of streptokinase.…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation